KONSTRUKSI SOSIAL IBU SEBAGAI MADRASAH UTAMA PERSPEKTIF SOSIOLOGI KELUARGA - Adawiyah, Robiatul; Agustin, Maulid (LPPM STAI Muhammadiyah Probolinggo, 2023)
This article discusses the role of mothers as the main educational agent in the family, serving as the first madrasah for children. Mothers not only educate children in academic aspects, but also in religious values, morals and life skills. Research shows that the education provided by mothers has a major influence on children's character development and moral understanding. However, mothers often face challenges in carrying out this role, such as dividing their time between work and household responsibilities. Support from husbands and government policies that support family welfare are essential to help mothers fulfill their roles well. The article also emphasizes the importance of providing better access to education for women so that they can contribute effectively to their children's education. In addition, the role of the media, religion and social institutions is crucial in reinforcing the social construction of mothers as primary educators. The media shapes society's views through representations of mothers, while religion emphasizes mothers' responsibilities in the moral and spiritual education of children. In the context of modern families, mothers face challenges in balancing traditional and modern roles, including role conflict and lack of support from social institutions. Therefore, it is important to provide adequate support for mothers so that they can optimally fulfill their dual roles.